Lymphoepithelial Cysts of the Pancreas: CT and MRI Features - Temel Tirkes; Aashish Patel; Harvey Cramer; Sehnaz Evrimler; John M. DeWitt; Mohammad Al-Haddad (European Medical Journal)
Objective: Describe CT and MRI features of the lymphoepithelial cyst (LEC) of the pancreas. Methods: The authors identified 13 cases of LEC by searching their institutional electronic medical archives from 2004 to 2020. All of the patients had CT scans and six patients had both a CT and MRI. The final diagnosis was established either by fine-needle aspiration with cytopathology (n=6) or surgical resection (n=7). Results: The mean diameter of the cysts was 36 mm (range: 6–93 mm). Almost all of the cysts were exophytic (92%) and solitary (85%), favouring the tail (54%) or body (38%) of the pancreas. LECs were either oval (62%) or round (39%) and had well-defined contours. All LECs showed T2 hyperintensity and T1 hypointensity; however, the signal was heterogeneous. Diffusion-weighted imaging showed restricted diffusion in all cases. On CT, LECs commonly showed complex fluid density (>15 HU) with no visible septation, enhancement or calcification. Conclusion: LECs have a distinguishing feature on MRI, which is restricted diffusion on diffusion-weighted imaging. This is presumably secondary to the presence of keratin, which can be a helpful feature differentiating LECs from other pancreatic cystic neoplasms. Besides this, LECs predominantly appear as solitary and exophytic lesions, with complex fluid density on CT and heterogeneous hypointense T1 and heterogenous hyperintense T2 signal on MRI.